Microbiological Evaluation of Spoilt Tomato (Lycopersicum esculentum) and Pepper (Capsicum Spp) Sold in Mandate Market, Ilorin, Kwara State, Nigeria - VE, Edem; AI, Elijah; AI, Yahaya; MN, Etukakpan (The Asia Journal of Applied Microbiology, 2022)
Tomato and pepper contribute significantly to diet as they are used as ingredients in food preparation. This study evaluated microbiological quality of spoilt tomato and pepper sold in Mandate Market using standard microbiological methods. Results of analysis of variance (ANOVA) showed that there were significant (p < 0.05) differences in total heterotrophic bacteria count (THBC), total coliform counts (TCC) and total fungal counts (TFC) of the samples under study. The results from spoilt tomato samples showed that THBC ranged from 1.7 ± 0.07×104 CFU/ml - 9.5±0.21×104CFU/ml, TCC from 0.0×104 CFU/100ml - 9.0×104 CFU/100ml, while TFC ranged from 1.1 ± 0.4×104 CFU/g - 4.1 ±1.27 ×104 CFU/g. THBC of spoilt pepper ranged from 1.7 ± 0.28 × 104 CFC/ml - 8.8± 0.21 × 104 CFC/ml. TCC was between 0.0×104CFU/ml and 6.0± 1.41 ×104 CFU/ml while TFC ranged from 1.5 ± 0.28 CFU/g - 5.5 ± 0.35 ×104 CFU/g. The probable microorganisms present in spoilt tomato samples include, pseudomonas vulgaris, pseudomonas aeruginosa, staphylococcus aureus, bacillus subtilis, Escherichia coli, C. freundi, Penicillium chrysogenum, Saccharomyces cerevisiae, Aspergillus niger and Rhizopus stolonifer. In addition, microorganisms identified from spoilt pepper samples were Clostridium sp, Pseudomonas aeruginosa, Staphylococcus aureus, Salmonella sp, E. coli, Aspergillus niger, Fusarium oxysporum, Penicillium sp. and Aspergillus fumigatus. The study revealed that E. coli and Staphylococcus aureus dominated spoilt tomato and pepper with prevalence of 33.4 % and 28.6 % respectively. Results on the survey showed poor handling, storage and hygienic practices of tomato and pepper vendors in Mandate Market.